A Comparative Analysis of the Organization of Turkic States: Population Size and Birth Rate as Indicators of Demographic Sustainability - Rostovskaya, Tamara K.; Sagynbayeva, Ayaulym; Suleymanli , Ebulfez (The New Research of Tuva, 2025)
This study considers the main indicators of demographic sustainability in the Republic of Azerbaijan, the Republic of Kazakhstan, the Kyrgyz Republic, Turkey, and the Republic of Uzbekistan, which are members of the Organization of Turkic States (OTS), an entity whose important area of activity is addressing and preventing demographic challenges. The countries are united by steady population growth; however, the dynamics vary significantly between them, which affects their demographic sustainability. The analysis focuses on population size and birth rates. The methodological framework of the research is based on demographic development concepts and the theory of demographic transition. The study covers the period from 2009 to 2023.Indicators of birth rates among the populations of these Turkic countries are typologized. It has been revealed that Turkey and Azerbaijan demonstrate population reproduction trends similar to those observed in European Union countries (low birth rates and postponement of first births to older age groups). It is found that Turkey’s socio-economic development indicators contribute to greater demographic sustainability compared to the other OTS countries. In several OTS countries, there are observed tendencies for emigration, which may adversely affect demographic sustainability.
Keywords: Organization of Turkic States; Azerbaijan; Kazakhstan; Kyrgyzstan; Turkey; Uzbekistan; demographic sustainability; birth rate; demographic transition